Sorption Ability of Bentonite Rocks from Yogyakarta to Eliminate the Radiocesium Elements in Solution - Heru Sriwahyuni; Budi Setiawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
This activity was to examine the ability of bentonite minerals from Yogyakarta to absorb the radiocesium contained in the solution. The purposes of the experiment were to determine sorption ability of bentonite mineral from Yogyakarta to absorb radiocesium in solution or groundwater and to enrich the Indonesia bentonite capability database to absorb radiocesium. The bentonite material was planned to be used as a buffer material of the engineered barrier system on the radwaste disposal facility in the future. The contact time, the presence of Na and K ions in the solution, as well as the variable of dissolved CsCl concentration were considered as experiment parameters. The value of Kd was also used as the indicator of radiocesium sorption into the bentonite samples. The experiment results shown that the maximum of Kd value was about 6800 mL/g for sample-1, and the presence of dissolved Na and K ions in the solution could reduce the values of Kd which were 800 and 300 mL/g for sample-1, respectively. Determination of isotherm sorption of radiocesium by bentonite from Yogyakarta was approximated by using linear equation or Freundlich law.